2019
DOI: 10.3389/fphar.2018.01578
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Canadian Pharmaceutical Alliance (pCPA): Timelines Analysis and Policy Implications

Abstract: This analysis follows our recent study showing that Canadian public reimbursement delays have lengthened from regulatory approval to listing decisions by public drug plans and delayed public access to innovative medicines, mainly due to processes following the Common Drug Review (CDR) and the pan-Canadian Oncology Drug Review (pCODR). Public drug plans participate in a pan-Canadian Pharmaceutical Alliance (pCPA) joint negotiation process before making decisions about whether or not to reimburse a product revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The anticancer drugs examined in this study were reimbursed at a median time of 669 days (mean = 687 days) after market approval. Although there are large variations in the time to reimbursement compared with that in other countries, the median period is significantly longer in Korea than in other countries (ranging from 89 days to 422 days) [ 13 , 14 ]. Overall, variations in the time of drug approval to patient access may be attributed to patient preferences, assessment criteria, and reimbursement schemes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer drugs examined in this study were reimbursed at a median time of 669 days (mean = 687 days) after market approval. Although there are large variations in the time to reimbursement compared with that in other countries, the median period is significantly longer in Korea than in other countries (ranging from 89 days to 422 days) [ 13 , 14 ]. Overall, variations in the time of drug approval to patient access may be attributed to patient preferences, assessment criteria, and reimbursement schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The Korean government spent an average of 601 days to make a reimbursement decision for new anticancer drugs between 2009 and 2014 [ 12 ]. Although there are large variations in the time to reimbursement compared with that in other countries, the median period for oncology drugs is still significantly longer in Korea than in other countries: 89 days in Canada, 212 days in France, 320 days in Spain, 321 days in the United Kingdom (UK), and 422 days in Italy [ 13 , 14 ]. Many cancers have a higher chance of being cured if diagnosed and treated early, so creating policies to expedite patient access to advanced anticancer drugs is critical for saving lives and reducing the overall societal economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…The Pan-Canadian Pharmaceutical Alliance faces challenges such as an increasing backlog of drugs awaiting negotiation and appears to be taking more time to initiate or decline negotiations. 31 There also seems to be lack of transparency in the negotiation process and in selecting the criteria informing the decision-making process. 31 Finally, the alliance only negotiates drug prices for public drug plans, which limits its negotiating power, as there are more than 100,000 private drug insurance plans in Canada that are excluded from the negotiations.…”
Section: Drug Spending In Canadamentioning
confidence: 99%
“…While the negotiated prices of generic medications are transparent and generally apply to the whole market, the negotiated prices of innovative medicines are confidential and only apply to the participating payers. Further, the pCPA does not publish formal review or negotiation timelines, nor the criteria used in decision-making [ 30 ]. Studies have suggested that the time from the CADTH pCODR recommendation to the pCPA negotiation publication for oncology drugs took as long as 371 days in 2016 [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the pCPA does not publish formal review or negotiation timelines, nor the criteria used in decision-making [ 30 ]. Studies have suggested that the time from the CADTH pCODR recommendation to the pCPA negotiation publication for oncology drugs took as long as 371 days in 2016 [ 30 ].…”
Section: Introductionmentioning
confidence: 99%